Perceived Benefits and Challenges of Management Graduates of Far Western University towards the Entrepreneurship Intention - Pant, Hari Shankar (Far Western Review, 2023)
Entrepreneurs are contributing a lot for the economic and social development of each country of world. The aim of this study is to explore perceived benefits and challenges of management graduates of Far Western University towards the entrepreneurial intention. Data were collected from 107 students who are currently studying M.Phil., MBA and MBS in central campus Far Western University. A set of questionnaires was designed as the main instrument of data collection which consist the 17 questions related to perceived strength, weakness, opportunities and threats (SWOT) of the respondents. Out of the 17 questions, first four are related to the opportunities, second five are related to challenges, third four are related to strength and last four are related to weakness. The instrument for data collection comprised of 6-point Likert type scale. To explore the perceived benefits and challenges of entrepreneurship intentions of management graduates of Far Western university descriptive statistics has been used. Data were processed by using computer software SPSS. The result indicates that ongoing rapid urbanization has perceived a great opportunity or highly motivates the students to start up business and financial problem is perceived as main obstacles to be an entrepreneur.